2015
DOI: 10.1589/jpts.27.2053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early physiotherapy with respect to severity of pneumonia of elderly patients admitted to an intensive care unit: a single center study in Japan

Abstract: [Purpose] We performed early physiotherapy for elderly patients with pneumonia admitted to an intensive care unit (ICU), and examined the effects of this early physiotherapy on the severity of pneumonia. [Subjects and Methods] Patients for whom physiotherapy was started the day after admission to the ICU (acute phase) were assigned to the early intervention group and compared with patients in the standard intervention group. All patients were divided into three groups (Groups I, II, and III) based on the sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Hospital‐based physical therapy had benefits in reducing the 30‐day hospital readmission rate of acutely ill older adults with CAP and declining physical function. Chigira et al also demonstrated the early physiotherapy may shorten the intensive care unit admission period and prevent decline in ADL in elderly patients 13 . In our hospitals, patients with pneumonia usually took part in some form of physical rehabilitation program administered by physicians or physical therapists within 7 days after hospitalization.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Hospital‐based physical therapy had benefits in reducing the 30‐day hospital readmission rate of acutely ill older adults with CAP and declining physical function. Chigira et al also demonstrated the early physiotherapy may shorten the intensive care unit admission period and prevent decline in ADL in elderly patients 13 . In our hospitals, patients with pneumonia usually took part in some form of physical rehabilitation program administered by physicians or physical therapists within 7 days after hospitalization.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies demonstrated that early physiotherapy may prevent decline in ADL in elderly patients with pneumonia. 11 , 12 , 13 Yagi et al assessed the effect of early rehabilitation on improving ADL in elderly patients with aspiration pneumonia. 11 They showed that the early rehabilitation group exhibited significant improvement in ADL (OR 1.57, 95% CI 1.50–1.64, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…World health organization (WHO) in 18 th of March (2020) applied messages for older adults, people with underlying health condition to learn simple daily physical exercises to perform at home, in quarantine or isolation so can maintain mobility and reduce boredom, while they applied messages for people in isolation to exercise regularly to improve mental health and psychosocial considerations during theCOVID-19 outbreak [9]. Chigira et al (2015) [10] performed early physiotherapy for elderly patients with pneumonia admitted to an ICU and examined its influence on the severity of pneumonia. They compared the results of the standard and early intervention groups.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies document the effects of early mobilisation (EM) of patients in the intensive care unit (ICU) and in surgery units, and seems as a safe and effective intervention that can have a significant impact on functional outcomes 9 , 10 , 11 , 12 , 13 ) . However, to our knowledge, only one study documents the effects of early mobilisation of patients with CAP 14 ) .…”
Section: Introductionmentioning
confidence: 99%